Case report: Radiopaque mandibular lesions in three dogs - Vesterinen, Senni; Sihvo, Hanna-Kaisa; Airas, Niina; Kuntsi, Helena (Frontiers in Veterinary Science, 2025)
Radiopaque lesions of the mandible are occasional findings in dental radiographs in dogs. The different diagnoses of densely sclerotic lesions in humans include odontoma, idiopathic osteosclerosis, condensing osteitis, hypercementosis, osteoma, osteoblastoma, and oral exostosis. Publications on many of these conditions in dogs are scarce. This clinical report describes three young adult dogs with radiologically and histologically similar radiopaque mandibular lesions that had either displaced or narrowed the mandibular canal. One dog showed symptoms that could have been consistent with neurological pain due to the lesion. Diagnostics included clinical examination, dental radiographs, cone beam computed tomography and histology. Radiographically and clinically, the lesions resembled human idiopathic osteosclerosis. Histology alone did not reveal a definitive diagnosis, but combining histology with clinical and radiographic data, the most likely diagnosis was idiopathic osteosclerosis. The dogs returned for follow-ups 6 months after the surgeries, and there was no evidence of additional growth in the remaining lesions.